Bad Measures Don’t Make Good Medicine: The Ethical Implications of Unreliable and Invalid Physician Performance Measures - Labig, Chalmer E. (Journal of business ethics, 2009)
Drawing on the performance appraisal and medical literatures, we examine representative ethical issues involved in current appraisal practices of individual physicians: the use of invalid and unreliable measures; organizational goals conflicting with patient health goals; using individual measures for what are group performance results; making individual attributions for what are systemic causes (and results); and using clinical feedback for organizational purposes. Suggestions for developing more ethical performance appraisals include reflecting upon the multiple purposes and means of appraisals, and the limitations of current practices. Greater understanding of the effects of current appraisal practices on physicians can help minimize its potentially adverse consequences on the delivery of quality healthcare.